Comprehensive quantum chemical analysis, vibrational spectroscopy, molecular docking, ADMET, and in vitro validation studies of hydroxychloroquine-MRGPRX2 complex in IDH-wildtype glioblastoma - Aliye Demet Demirag; Rahmi Atil Aksoy; Gizem Akman; Vildan Kaya; Mustafa Yildirim (PLoS ONE, 2026)
Glioblastoma is an aggressive astrocytic neoplasm characterized by significant intratumoral heterogeneity and resistance to standard therapies. Despite advances such as the Stupp protocol, the prognosis remains poor, with a median survival of 12–15 months. Mast cells in the tumor microenvironment (TME) release pro-inflammatory mediators, promoting tumor progression and therapeutic resistance. The Mas-related G protein-coupled receptor X2 (MRGPRX2), expressed on mast cells, is implicated in neuroinflammatory regulation. This study evaluates hydroxychloroquine (HCQ), a 4-aminoquinoline derivative, as a potential MRGPRX2 inhibitor using a comprehensive multidisciplinary approach. Density Functional Theory (DFT) at the B3LYP/6–31 + G(d,p) level was employed to analyze the structural and electronic properties of HCQ, validated by FTIR and Raman spectroscopy. To ensure statistical robustness and address receptor specificity, 100 independent blind docking simulations were performed using the high-resolution MRGPRX2 structure (PDB ID: 7S8L). The docking protocol was rigorously validated through a cross-docking study using the 7S8N reference ligand, yielding a high spatial consensus with an RMSD of 3.06 Å. The results revealed that HCQ possesses a superior binding affinity of −7.0 kcal/mol, while comparative docking with the standard therapeutic Temozolomide (TMZ) yielded a lower affinity of −5.6 kcal/mol. Detailed residue-level analysis highlighted a distinct binding fingerprint for HCQ, involving specific interactions with residues such as Tyr137, Ser130, and Phe64, which were notably different from the TMZ-receptor complex. ADMET profiling confirmed HCQ’s favorable pharmacokinetic properties and its potential to cross the blood-brain barrier. In vitro validation on U87-MG glioblastoma cells demonstrated a time-dependent cytotoxic effect, where HCQ significantly reduced cell viability to approximately 70% at 72 hours (p < 0.01). This biological activity directly correlates with the strong binding profile and high affinity observed in the 100-run docking analysis . Our findings suggest that HCQ is predicted to interact with MRGPRX2 with a high binding affinity, supporting further functional validation and providing a novel structural basis for targeting mast cell-mediated neuroinflammation in glioblastoma treatment. These results advocate for the repositioning of HCQ as a targeted adjuvant therapy to overcome conventional treatment limitations.